AB0273 Methylentetrahydrofolate Reductase C677T Gene Polymorphism is Associated with Progressive Joint Destruction and Anti- Cyclic Citrullinated Peptide (ACCP) Positivity in Patients with Early Rheumatoid Arthritis. (9th June 2015) - Guseva, I.; Demidova, N.; Soroka, N.; Luchikhina, E.; Alexandrova, E.; Novikov, A.; Samarkina, E.; Fedorenko, E.; Lukina, G.; Trofimov, D.; Karateev, D.; Nasonov, E.
Abstract : Background: The recent evidence suggests that clinical effectiveness of methotrexate might not be always accompanied by slowing the progression of joint damage in patients with rheumatoid arthritis. Thus, the search of reliable prognostic biomarkers to predict a progressive joint destruction is of significant clinical relevance. One of the key enzymes involved in methotrexate metabolism is methylentetrahydrofolate reductase (MTHFR). We studied the MTHFR gene polymorphisms 677C/T (rs1801133) and 1298 A/C (rs1801131) in relation to radiographic disease progression and ACCP positivity, which is a well-known predictor of joint destruction. Objectives: To compare the distribution of 677C/T and 1298 A/C genotypes in early RA patients (eRA pts) and healthy donors (controls), as wells as in the sub-groups of eRA pts with and without ACCP. We also studied the link between radiographic progression of joint damage and 677C/T and 1298 A/C polymorphisms. Methods: One hundred twenty two pts (21 male, 101 female) with eRA (ACR 1987 criteria; disease duration less than 2 years) were enrolled into a 4-year prospective study. The mean age of eRA pts was 48, 9±13, 4 years. At the time of enrollment disease duration was 7, 5±6, 1 months, and none of the patients had received disease-modifying antirheumatic drugs (DMARDs) or corticosteroids. During the study most of the patients were treated with methotrexate (alone or in combination with other DMARDs). 309 healthy blood donors were included as controls. Results: The distribution of 677C/T and 1298 A/C genotypes not differed significantly between eRA pts and controls. Stratification of the patients in terms of ACCP–positivity revealed that these pts groups had a statistically significant difference in 677C/T genotype distribution (Table ), while they did not show any difference in 1298 A/C genotypes (p<0, 003 and p>0.05, respectively). TT genotype was linked to ACCP-negative disease (OR=2, 9 [1, 3-6.8], p<0, 009, pcorr <0, 018). At the time of enrollment, 18, 7% of eRA pts had radiographic erosive changes in the small joints of the hands and feet; 4 years later these findings were noticed in 78, 3% of the patients. The radiographic progression of joint damage as a binary variable was associated with 677C/T polymorphism (OR=4, 5, p=0, 015) and ACCP-positivity (OR=22, 5, p=0, 0001). During a 4-years' follow-up the negative influence of ACCP-positivity on the extent of X-ray disease progression was modified by 677C/T polymorphism (delta total Sharp score: ACCP+/CC/CT-18.0 [11.0-26.0], ACCP+/TT-15, 5 [4.5-25.8], ACCP-/CC/CT–8.5 [2.3-12.0], ACCP-/TT–4.0 [2.0-8.0]; delta erosions Sharp score: ACCP+/CC/CT–5.0 [3.0-8.0], ACCP+/TT–3.5 [0.8-5.5], ACCP-/CC/CT–0.0 [0.0-2.0], ACCP-/TT–0.0 [0.0-1.0]). Conclusions: Our data suggests that polymorphism of MTHFR C677T gene is closely linked with ACCP-status and significantly contributes into ACCP negative impact on the extent of radiographic disease progression. Disclosure of Interest: None declared